Immunological Aspects of Fulminant Type 1 Diabetes in Chinese. (14th February 2016) - Wang, Zhen; Zheng, Ying; Tu, Yiting; Dai, Zhijie; Lin, Jian; Zhou, Zhiguang
Abstract : Background. Fulminant type 1 diabetes (FT1D) is a novel subtype of type 1 diabetes characterized by extremely rapid onset and complete deficiency of insulin due to the destruction of pancreatic β cells. However, the precise mechanisms underlying the etiology of this disease remain unclear. Methods. A total of 22 patients with FT1D and 10 healthy subjects were recruited. Serum antibodies to GAD, IA2, and ZnT8 in patients were tested. And peripheral T cell responses to GAD65, insulin B9–23 peptide, or C peptide were determined in 10 FT1D patients and 10 healthy controls. The mRNA levels of several related cytokines and molecules, such as IFN- γ, IL-4, RORC, and IL-17 in PBMCs from FT1D patients were analyzed by qRT-PCR. Result. We found that a certain proportion of Chinese FT1D patients actually have developed islet-related autoantibodies after onset of the disease. The GAD, insulin, or C peptide-reactive T cells were found in some FT1D patients. We also detected a significant increase for IFN- γ expression in FT1D PBMCs as compared with that of healthy controls. Conclusion. Autoimmune responses might be involved in the pathogenesis of Chinese FT1D.